JENIS DAN KELIMPAHAN FITOPLANKTON SERTA PERIFITON EPILITIK DI PERAIRAN SUNGAI KAMPAR KANAN KELURAHAN AIR TIRIS KECAMATAN KAMPAR KABUPATEN KAMPAR PROVINSI RIAU - Syafriwarty Syafriwarty; Nur El Fajri; Adriman Adriman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTKampar Kanan River has strong current and rocky substrate and it may affect the type and abundance of phytoplankton and ephylitic periphyton. To understand the type and abundance those organisms, a study has been conducted in February to March 2017. Parameter measured were types and abundance the phytoplankton and ephylitic periphyton, temperature, brightness, current, depth, pH, DO, free CO2, nitrate and phosphate.Samplings were conducted 3 times, once/ week, in 3 stations.Results shown that there were 38 phytoplankton species present, namely Bacillariophyceae (16 species), Chloropyhceae (14 species) , Cyanophyceae (4 species) ,Euglenophyceae (2 species), Chrysophyceae and Dinophyceae (1 species).  The average of phytoplankton abundance was around 2,023to 2,252  cells/L. the H’ was 4.465to 4.624; C was 0.071to 0.115  and E was 0.765to 0.840. Results shown that there were 45 the ephylitic periphyton species present, namely Bacillariophyceae (23species), Chlorophyceae (18species), Cyanophyceae (3species), andXantophyceae (1 species). The average the ephylitic periphyton abundance was 5,322to 8,479  cells/ cm2. The H’ was 3.725to 4.469; C was 0.071to 0.115  and E was 0.765 to 0.840. Based on the abundance of phytoplankton and ephylitic periphyton, the Kampar River in the Air Tiris Village is classified as moderate fertility rate.Keywords: Phytoplankton, ephylitic periphyton, Air Tiris Village Kampar River, Water Quality